Kebijakan Dinas Sosial Kota Ternate terhadap Pelaksanaan Pelayanan Sosial kepada Anak Yatim, Piatu, dan Yatim Piatu - Mohbir Umasugi (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This study aims to analyze the policy of the Tenate City Social Service regarding the Implementation of SocialServices for Orphans. The data analysis method used in this research is descriptive qualitative. The results of thestudy showed that there were 244 orphans, orphans and orphans in Ternate City with details of 123 orphans, 35orphans and 86 orphans. Of all the orphans, orphans and orphans, they have received social services from the TernateCity Social Service in the form of a tiered formal education assistance program starting from elementary, junior high,up to high school, then social services in the form of assistance to the individual child's social life and orphanslivelihoods, orphans and orphans so that they feel protected in terms of safety, security, order and inner and outerpeace, as well as self-confidence. Meanwhile, in terms of entrepreneurship, it is a facility that supports orphans,orphans and orphans through training programs as well as entrepreneurial practices which are expected to be able tocreate a generation of people who are independent in facing the increasingly competitive world of entrepreneurship.